Dietary inflammatory index and healthy eating index-2015 are associated with rheumatoid arthritis. Issue 18 (16th December 2021) - Jandari, Sajedeh; Mosalmanzadeh, Negin; Shadmand Foumani Moghadam, Mohammad Reza; Soleimani, Davood; Shivappa, Nitin; Hébert, James R; Jokar, Mohammadhassan; Karamati, Mohsen; Abedi, Samine Sadat; Malek, Nafiseh; Rezvani, Reza
Abstract: Objective: Many arthritic patients have the belief that dietary habits can worsen or ameliorate their symptoms. Whether diet quality can modify the risk of rheumatoid arthritis (RA) is an issue of continued scientific debate and interest. Therefore, we aimed to examine the association between both overall diet quality and the overall diet inflammatory potential on the risk of RA. Design: Overall diet quality and the overall inflammatory potential of the diet were evaluated with the use of Dietary Inflammatory Index (DII) and the Healthy Eating Index (HEI)-2015, respectively. Both DII and HEI-2015 scores were calculated based on a validated semi-quantitative FFQ. Multivariable-adjusted odds of RA were calculated across tertiles of HEI, and energy-adjusted DII (E-DII) scores using binary logistic regression. Setting: Mashhad, Iran. Participants: Fifty newly diagnosed RA cases and 100 well-matched healthy people controls. Results: Individuals in the highest tertile of DII scores, indicating the most pro-inflammatory diet, were about three times more likely to have RA than those in the lowest tertile (OR: 2·99; 95 % CI 1·08, 8·24; P -trend: 0·037), whereas individuals in the highest tertile of HEI scores, indicating more top dietary quality, had a significantly lower odds of RA than those in the lowest tertile (OR: 0·33; 95 % CI 0·12, 0·87; P -trend: 0·024). Conclusions: Our findings show that E-DII and HEI-2015 are positively and negatively associated, respectively, with the odds of RA in a convenience sample of Iranians. These results highlight the importance of overall diet quality in modulating the risk of RA.